Conceptual Study of Hridroga with its Clinical Management- An Ayurvedic Approach - Taru Prajakta,; More Shweta, (International Journal of Ayurveda and Pharma Research, 2022)
Hridroga (heart diseases) is one of the major causes of death in India. Hridroga means Cardiac Disorders in Ayurveda. Heart is described as Marma (vital organ) in Ayurveda. Number of people suffering from the heart diseases are quite increased in last few years. According to the global burden of disease, the 24.8 % of all deaths are occurred due to CADs [1] and it affects elders as well as young population, so it is needed to review the concept of Hridroga and its management according to Ayurvedic perspectives with its present updates so, one can prevent these conditions or manage them with more precise approach. Previously number of works has been done on Hridroga in relation to its pathology, treatment aspect, dietary regimen useful for pathological conditions affecting heart. Detail description of causes, symptoms, treatment part of Hridroga is available in the Ayurvedic texts. Ayurveda explains in detail regarding how Ayurveda is afflicted with vitiated Vata, Pitta and Kapha with its symptoms and clinical management. To prevent these conditions and also treat them with more precise approach the review of these concepts is helpful. This article includes the etiological factors, Dosha specific symptoms, types and clinical management of Hridroga (heart disorders) as explained in Ayurvedic texts.